DOP087 The gut microbiota of pregnant women with Crohn's disease and their babies is associated with abnormalities in the adaptive immune system: results from the MECONIUM study. (16th January 2018) - Torres, J; Seki, A; Tarassishin, L; Hu, J; Eisele, C; Nair, N; Britton, G J; Mao, Q; Mogno, I; Clemente, J C; Faith, J; Colombel, J -F; et al.
Abstract: Background: Prenatal (maternal) and early life bacterial colonisation is thought to play a major role in shaping the infant′s mucosal and systemic immune system. Furthermore, accumulating evidence links early life exposures, many of which are known to impact the gut microbiota development assemblage and development (e.g. antibiotics, C-section, breastfeeding), to the risk of developing IBD later in life. To understand how the gut microbiota during pregnancy and in early life may affect the immune system development, we colonised germ-free mice (GFM) with the stool from the third trimester of pregnant women with and without Crohn's disease (CD) and their 3-month old babies. Methods: Stool from 8 pregnant women with CD and their babies (16 individuals) and stool from three control women and their babies (6 individuals) were transplanted into 5-week-old C57BL/6 GFM and sacrificed 5 weeks later. Mononuclear cells harvested from the colon lamina propria (CLP) were collected for multiparameter flow cytometric analyses and immune profiling of the innate and adaptive immune systems. Feces were collected from mice at the time of sacrifice and sequenced for 16 srRNA. Results: Mice inoculated with stool from pregnant women with CD and their babies presented significant differences in their microbial gut diversity as compared with those inoculated with control samples ( p < 0.001) (Figure 1). Mice colonised with stool from CD donors presented a significantly lower frequency of switched memory B cells (CD19+CD27+IgM-IgD-) and of TREG (CD3+CD4+FoxP3+) as compared with mice colonised with stool from pregnant control women (Figure 1). GFM colonised with stool from babies born to CD mothers presented a significantly lower frequency of switched memory B cells (CD19+CD27+IgM-IgD-) as compared with those colonised with stool from babies born to control mothers ( p < 0.01; Figure 2). Conclusions: The microbiome of pregnant donors with IBD and their offspring triggers development of suboptimal adaptive immune system in GFM. Abnormal imprinting of the neonatal immune system in babies born from mothers with IBD could contribute to predisposition to IBD later in life.